Karakterisasi dan penentuan formulasi terbaik bodyscrub berbasis ampas kelapa dengan penambahan esktrak bunga telang (Clitoria ternatea) - Nina Hairiyah; Raden Rizki Amalia; Nuryati Nuryati (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Bodyscrub is a skin care product that consists of exfoliants and active ingredients. In this research, the process of making a body scrub was carried out using an exfoliant in the form of coconut dregs flour and the addition of the active ingredient, butterfly pea flower extract (Clitoria ternatea). The aim of this research is to characterize and determine the best formulation of bodyscrub products produced with the addition of 0 %, 10 %, 15 % and 20 % butterfly pea flower extract. Characterization was carried out using pH parameters, emulsion stability test, homogeneity test, spreadability test, skin irritation test, and skin moisture effectiveness test. Determining the best formulation was carried out using hedonic and Bayes methods. The results of the research showed that all bodyscrub formulations met the SNl 16–4399–1996 standards regarding sunscreen preparations, had good emulsion stability, did not cause irritation and it was seen that the addition of butterfly pea flower extract was able to make the skin more moisturized through a skin moisturizing effectiveness test. The results of the hedonic test and Bayes test showed that the formulation most preferred by the Panelists and the calculation to determine the best formulation for this coconut dregs flour bodyscrub preparation was with the addition of 20 % extract.